Dithiophosphinate-bridged ruthenium(I) and ruthenium(II) complexes. The structure of [(Ru2(CO)4(.mu.-S2PMe2)2(PPh3)2].cntdot.1/2CH2Cl2 - Hilts, Robert; Cowie, Martin (My University, 1990)
Replacement of the bridging acetate groups in [Ru2(C0)4(M-02CMe)2(PR'2R")2] (R', R" = Ph, Me) by the dithiophosphinate anions R2PS2‘ (R = Me, Ph) yields a new class of dithiophosphinate-bridged Ru(I) complexes, [Ru2(CO)4(m-S2PR2)2(PR'2R")2]· Although the Ru-Ru bond in these species can be reversibly protonated, it does not react with [Au(PPh3)][BF4], diazomethane, or dimethyl acetylenedicarboxylate. Reaction of the related acetate-bridged species [Ru2(C0)4(M-02CMe)2(NCMe)2] with NaS2PMe2 does not yield the expected dithiophosphinate-bridged product but instead gives the mononuclear species [Ru- (CO)2();2-S2PMe2)2] along with Na2S, Na02CMe, MeCN, and Me2P(S)P(S)Me2. An X-ray structure determination of [Ru2- (CO)4(M-S2PMe2)2(PPh3)2]>1/2CH2Cl2 confirms the dithiophosphinate-bridged formulation and shows a long Ru-Ru separation of 2.9000 (6) A and a twisting about the metal-metal axis by ca. 39°. This compound crystallizes in the monoclinic space group P2,/c with cell parameters a = 15.182 (3) A, b = 18.230 (4) A, c = 18.082 (4) A, ß = 94.23 (2)°, and Z = 4. Refinement has converged at R = 0.054 and /?w = 0.082 on the basis of 5928 unique reflections and 365 parameters varied.